Hardness Analysis of blacksmith Knife on Heat Treatment Process - Am. Mufarrih,Yasinta Sindy Pramesti,Wahyu Eko Prasetyo,Suryo Widodo,Agus Seto Nugroho (International Conference on Industrial Revolution for Polytechnic Education, 2021)
The process of heat treatment carried out in blacksmith SMEs is still simple by using ordinary water coolers. This causes the knife to crack easily. This study aims to determine the effect of temperature variations in heat treatment and cooling media on the knife hardness produced by blacksmith SMEs. The experimental design used the L16 factorial method. Data analysis used Two Way ANOVA. The independent variables varied were temperature (100, 200, 300, 400 ° C) and cooling media (air, ordinary water, oil, limewater), while the dependent variable of this study was knife hardness. Data collection of hardness used Rockwell test equipment as much as 6 data for each materials. The results showed that there was an effect of temperature variation and cooling media on knife hardness. The highest average hardness value of 59 HRC was obtained at a temperature variation of 400 ° C by using limewater cooling. Increasing the temperature of the heat treatment will increase the knife hardness.